Empowering Local Businesses: Evaluating Strategies and Proposing Solutions for Sustainable Growth of Micro, Small, and Medium Enterprises (MSMEs) in Cibeuruem Village - Maulana, Hasan Tafsir; Sudiapermana, Elih; Sulistiono, Eko (Economic Education and Entrepreneurship Journal, 2024)
MSMEs are an important sector to advance the economy in Indonesia, MSMEs in Cibeureum Village have great potential to be developed, totaling around 173 MSMEs, many development efforts have been made. However, these efforts have not made much positive contribution. The purpose of this article is to analyze what is happening with the efforts that have been made and provide alternative solutions in answering the problem. existing. Using a qualitative approach, data collection using secondary and primary data. Data collection techniques using interviews, observation and documentation. Then to analyze the data that has been obtained using an interactive model, namely data collection, data reduction, data presentation and conclusion drawing. The results of this study state that efforts to develop MSMEs through training are not in accordance with training procedures, have not applied the principles of empowerment and lack of collaboration with all elements of the pentahelix. As for bridging all elements of the pentahelix, it is necessary to have an assistance team called Sahabat UMKM as an alternative solution to be able to carry out and succeed development efforts in the future. So that this research can be used to improve MSME development programs and can be a consideration for all parties who will carry out programs according to procedures. In the future, it is expected to further adjust Sahabat UMKM by optimizing the available human resources so that the application of the pentahelix elements is better.Keywords: Training, Empowerment Principles, Pentahelix, MSMEsDOI: http://dx.doi.org/10.23960/E3J/v7i1.48-56